Joomla! 2.5 beginner's guide : an easy to use step-by-step guide to creating perfect websites with the free Joomla! CMS - Tiggeler, Eric (Community experience distilled., 2012)
Written with a fast-paced but friendly and engaging approach, this Packt Beginner's guide is designed to be placed alongside the computer as your guide and mentor. Step-by-step tutorials are bolstered by explanations of the reasoning behind what you are doing. You will quickly pick up the necessary skills, tips, and tricks for building a successful Joomla! website. This book is written for beginners to website design. By the end of the book you will have built a complete custom content managed website, and be ready to build any kind of website.